Intra-Firm Wage Differentials between German and Non-German Employees - Clemens Ohlert; Miriam Beblo; Elke Wolf (Verein für Socialpolitik, 2010)
In this paper, we analyse the wage differentials between employees of German and Non-German nationality using linked employer-employee data (LIAB) for the period 1996 to 2007. By focussing on the establishment level, we explicitly consider the heterogeneity of wage setting processes within firms. Our results show that the absolute pay gap within firms (of 11.3 percent on average) is about 5 percentage points smaller than the pay gap on the labour market as a whole, thus pointing to a sorting of Non-German workers into low-paying firms. The observed wage differentials are for the most part (8.8 percentage points) explained by differences in education and work experience. When distinguishing between subgroups we find the unexplained wage gap for immigrants from transition countries (predominantly Eastern Europe and Asia) to be larger on average than for immigrants from guest worker countries. A subsequent analysis of the relationship between selected firm characteristics and the unexplained intra-firm wage differentials reveals that Non-German employees face significantly lower wage discounts in firms with a high share of exports, a high share of Non-German employees and those covered by collective bargaining agreements.
Keywords: J15; J31; J71; 330; immigrant workers; within-firm wage differentials; unions; works councils